2016
DOI: 10.2298/sarh1612580s
|View full text |Cite
|
Sign up to set email alerts
|

Self-perception and satisfaction with dental appearance and aesthetics with respect to patients’ age, gender, and level of education

Abstract: Female respondents were more dissatisfied with their dental appearance and aesthetics as compared with male respondents, but the difference was found to be non-significant. Patients with higher education level were more satisfied with their dental appearance and aesthetics than those with lower education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
3
16
1
1
Order By: Relevance
“…Or is it simply that dental students comprise a special group in this respect? The 2016 study of Strajnic and colleagues [26] failed to find gender difference in self-perception and satisfaction with dental appearance in patients (i.e. laypersons), which supports the former hypothesis.…”
Section: Discussionmentioning
confidence: 81%
“…Or is it simply that dental students comprise a special group in this respect? The 2016 study of Strajnic and colleagues [26] failed to find gender difference in self-perception and satisfaction with dental appearance in patients (i.e. laypersons), which supports the former hypothesis.…”
Section: Discussionmentioning
confidence: 81%
“…It can be argued that advanced cognition may dominate effects of cultural or behavioral factors that have effect on selfperception of appearance. 14 In this study, high percentage of participants with bachelor's level of education was significantly more satisfied with their dental appearance during smiling compared to the other educational categories, while tooth color did not show to vary between different educational levels. On the contrary, previous reports have suggested that respondents with high education levels were more satisfied with the color of their teeth and had no desire for whiter teeth than those with lower levels of education.…”
Section: Figs 2a To C: Different Colors Of Teethmentioning
confidence: 48%
“…Perceived smile and appearance differs between individuals as well as in populations. 13,14 This study demonstrated that 39.4% of the participants were dissatisfied with the color shade of their teeth. This finding is lower than Turkish 55.1% 15 and Chinese 52.6% 16 studies and higher than that reported in United States 34%.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations